Pulmonary hypertension in POEMS syndrome - Li J; Zhuang Tian; Haiyan Zheng; Wen Zhang; Minghui Duan; Y.-T. Liu; Xinxin Cao; Daobin Zhou (2012)
POEMS syndrome is a rare clonal plasma cell disease. Patients with POEMS syndrome are at risk of developing pulmonary hypertension, but the data on its incidence and impact on outcome are limited. We reviewed records of 154 POEMS syndrome patients with complete duplex echocardiography data for estimation of pulmonary artery systolic pressure (sPAP) at the time of diagnosis. Forty-two (27%) of 154 patients with pulmonary hypertension (estimated sPAP ≥50mmHg) were identified. Median age was 46 years (range 31–71 years). Patients with pulmonary hypertension were more likely to have peripheral edema (P=0.04), ascites (P=0.02), pleural effusion (P=0.005), and have longer time from onset to diagnosis (P=0.004) when compared with those without pulmonary hypertension. Restrictive abnormalities and decreased diffusion capacity of carbon monoxide were observed in 83% and 96% patients with pulmonary hypertension, compared with 50% and 72% in patients without pulmonary hypertension, respectively. Reversibility of pulmonary hypertension was observed after treatment of POEMS syndrome. After median follow of 32 months, survival of patients with pulmonary hypertension was worse than those without (median overall survival 54 months vs. median not reached, P=0.021). In conclusion, pulmonary hypertension is a common feature of POEMS syndrome, and is associated with signs of extravascular volume overload. Although active treatment of POEMS syndrome can reverse pulmonary hypertension, survival of these patients is worse than those without pulmonary hypertension.